2016
DOI: 10.3897/phytokeys.75.9837
|View full text |Cite
|
Sign up to set email alerts
|

Borneocola (Zingiberaceae), a new genus from Borneo

Abstract: A new genus from Borneo, Borneocola Y.Y.Sam, is described here. The genus currently contains eight species previously classified as members of the Scaphochlamys Baker. The finding is based on the results of the morphological and molecular studies of Scaphochlamys throughout its geographical range and its closely allied sister groups, Distichochlamys M.F.Newman and Myxochlamys A.Takano & Nagam. Borneocola is nested within the tribe Zingibereae and its monophyly is strongly supported by both ITS and matK sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The genus closely resembles Scaphochlamys and phylogenetic studies have confirmed both as distinct sister-clades in the family Zingiberaceae (Kress et al 2002; Ngamriabsakul et al 2004; Takano and Nagamasu 2007; Sam et al 2016). There are several characters to distinguish Distichochlamys from Scaphochlamys , i.e.…”
Section: Taxonomymentioning
confidence: 84%
“…The genus closely resembles Scaphochlamys and phylogenetic studies have confirmed both as distinct sister-clades in the family Zingiberaceae (Kress et al 2002; Ngamriabsakul et al 2004; Takano and Nagamasu 2007; Sam et al 2016). There are several characters to distinguish Distichochlamys from Scaphochlamys , i.e.…”
Section: Taxonomymentioning
confidence: 84%
“…Borneocola was described from a clade of Scaphochlamys species endemic to Borneo, supported by molecular phylogenetic analyses and floral morphological characters (Sam et al using the plastid matK and nuclear ITS regions). However, in a subsequent revision of Bornean Scaphochlamys , in which twenty‐four species were recognised, Ooi et al () suggested that the sampling of only six to seven Bornean species in the analyses of Sam et al () was inadequate for supporting the formation of their new genus.…”
Section: A Working Synopsis Of the Bornean Endemic Plant Generamentioning
confidence: 98%
“…Borneocola was described from a clade of Scaphochlamys species endemic to Borneo, supported by molecular phylogenetic analyses and floral morphological characters (Sam et al using the plastid matK and nuclear ITS regions). However, in a subsequent revision of Bornean Scaphochlamys , in which twenty‐four species were recognised, Ooi et al () suggested that the sampling of only six to seven Bornean species in the analyses of Sam et al () was inadequate for supporting the formation of their new genus. The taxonomic concepts of the two studies were also incongruent – while Sam et al () recognised Borneocola as a clade sister to Myxochlamys A.Takano & Nagam., Ooi et al () recognised six different morphological groupings of Bornean Scaphochlamys throughout which the species of Borneocola sensu Sam et al () were scattered, such that accepting the genus Borneocola would render the rest of the Bornean Scaphochlamys species difficult to define within their morphological framework.…”
Section: A Working Synopsis Of the Bornean Endemic Plant Generamentioning
confidence: 98%
See 1 more Smart Citation
“…The clade is sister to Distichochlamys M.F. Newman (Takano & Nagamasu 2007;Sam et al 2016). Scaphochlamys is distinguished from Myxochlamys and Distichochlamys by the following combination of characters: petiole base pulvinate (Borneo only), spiral floral bract arrangement, flowering acroscopic, first bracteole 2-keeled and arising opposite to the bract, bracteole split to the base and anthers with free basal spurs (Searle 2010).…”
Section: Introductionmentioning
confidence: 99%